2011
DOI: 10.2106/jbjs.i.01241
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Tibiofemoral Contact Mechanics Following Radial Split and Vertical Tears of the Medial Meniscus

Abstract: Radial split tears of the medial meniscus that extend from the inner rim to the peripheral third of the meniscus do not cause significant changes in joint contact area and pressure. Vertical tears of the medial meniscus cause nonsignificant increases in joint contact pressure and reductions in contact area in the medial and lateral compartments.Repair of the vertical tear reverses these contact changes, resulting in contact pressure and area similar to the intact state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 12 publications
3
69
0
Order By: Relevance
“…Recently, there has been an increased effort to determine a more durable alternative to meniscectomy, because the procedure results in higher contact stresses at the articular surface of the knee [1,2,7,15,16,23,25]. Meniscal repairs have been extensively studied but continue to fail for varied reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, there has been an increased effort to determine a more durable alternative to meniscectomy, because the procedure results in higher contact stresses at the articular surface of the knee [1,2,7,15,16,23,25]. Meniscal repairs have been extensively studied but continue to fail for varied reasons.…”
Section: Discussionmentioning
confidence: 99%
“…One treatment option for the injured meniscus is partial or total meniscectomy, although well-established data suggest that increased contact stresses occurring long term can lead to poor outcomes in many cases [2,3,11,[23][24][25]. Such findings have led to a renewed focus on meniscal preservation strategies to prevent articular cartilage degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…By assuming that a normal lamellar layer is relatively homogeneous and somewhat stiffer than underlying layers, it would be logical that a thicker layer would result in higher indentation stiffness. Also, we presume that, even within an individual, the lamellar layer thicknesses could vary depending on meniscal regions such as anterior, middle, and posterior horn because the compressive loading is known to be heterogeneous throughout the meniscus (23).…”
Section: Comparison Of Mean Values Of Normal and Abnormal Samplesmentioning
confidence: 99%
“…In biomechanical studies, peak contact pressure was shown to increase by up to 235% after total meniscectomy9,10) and by up to 165% even after partial meniscectomy10). In contrast, the contact pressure after meniscal repair decreases almost down to the intact level10,11,12). In terms of clinical outcomes, meniscectomy has been associated with lower clinical outcome scores than meniscal repair13,14,15).…”
Section: Introductionmentioning
confidence: 99%